Catalytic reduction of benzaldehyde using green synthesized cuprous oxide nanoparticles - Samina Ferdousi; Mohammad Saiful Alam; Ershad Ahmmed; Razia Sultana Brishti; Md. Abu Rayhan Khan (Results in Chemistry)
Green approach was utilized for the synthesis of Cu2O nanoparticles (NPs) using aqueous leaf extract of Epipremnum aureum and characterized further to understand its particle size, surface morphology, crystallinity, and associated functional groups. XRD pattern of NPs ratified hexagonal crystal structure with average crystallite size to be 56.25 nm, and SEM image divulged porous surface area with grain size to be 70.37 nm. The TEM analysis showed the spherical size of NPs with the average size of 10.87 nm. The thermal stability of Cu2O NPs was observed to be 150 °C. Moreover, the present finding revealed low band gap (2.82 eV) of Cu2O NPs. The synthesized Cu2O NPs were employed for catalytic reduction of benzaldehyde to benzyl alcohol, and significant catalytic efficacy (39 %) was noticed in presence of ethanol. The Cu2O NPs showed significant catalytic activity (34 %) after four cycles along with slight aggregation of NPs possessing the particle size of 103.43 nm.